The Dynamics of State Authority Immunity in Administrative Justice - Gedmintaitė, Audronė; Masnevaitė, Elena; Paužaitė-Kulvinskienė, Jurgita (Teisė, 2025)
In an effort to strengthen the protection of human rights and legitimate interests, contemporary Lithuanian administrative justice has confidently gone beyond the boundaries of formal control. When examining complaints, the pursuit of not only legality but also justice in the relationship between individuals and the State becomes a central task for administrative courts in reviewing the actions of public administration. However, the benefits of such advanced judicial oversight will be limited if it remains inaccessible to certain categories of complaints in practice. The gaps in the right to seek judicial review in Lithuania can be reasonably linked to the increasingly frequent questions raised in administrative courts regarding the actions (or inactions) of the executive and legislative powers that violate individual rights and freedoms. Therefore, it is currently crucial to reassess the jurisdiction of administrative courts and their limits, especially in relation to the doctrines of immunity of State authority acts. This article analyses how administrative courts ensure the right to judicial protection for interested parties when individual rights and freedoms are violated due to the actions or inactions of the President, the Government, or the Parliament of the Republic of Lithuania.
Keywords: administrative justice; immunity of State authority acts; right to seek judicial protection; administrative proceedings; protection of human rights and freedoms